Effect of Teucrium Polium-Containing Chewing Gum on Reducing Salivary Streptococcus Mutans Counts - Somayeh Khoramian Tusi; Ahmad Jafari; Seyed Mahmoud Amin Marashi; Salomeh Faramarzi Niknam; Malihe Farid (Mashhad University of Medical Sciences, 2018)
Introduction: Several studies have reported the antibacterial effect of Teucrium polium extract. In this study, we sought to determine the effect of a chewing gum containing the aqueous extract of Teucrium polium on the level of salivary Streptococcus mutans. Materials and Methods: In this double-blind clinical trial, 20 dental students were randomly assigned to two groups of intervention and control. The intervention group received a chewing gum containing the aqueous extract of Teucrium polium, and the control group received a chewing gum without any plant extract. Each person chewed the gum for 20 minutes three times a day (after each meal) for three weeks. Unstimulated saliva samples were collected at the beginning of the experiment before the use of the gums and one day after the final gum consumption. The quantitative polymerase chain reaction (qPCR) technique was employed to determine the bacterial level. The colonization rate of Streptococcus mutans was compared between the two groups by using t-test in SPSS, version 21. Results: There was no significant difference between the two groups in terms of Streptococcus mutans counts before the intervention (P>0.05). The consumption of Teucrium polium extract-containing chewing gum in comparison with the placebo gum significantly diminished the number of Streptococcus mutans colonies (P=0.002). Conclusion: The results of this study showed that the chewing gum containing the aqueous extract of Teucrium polium significantly lowered the colonization rate of Streptococcus mutans in human saliva.